(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The Writ of Mandamus has played a fundamental role in the promotion of individual and collective rights in Brazil since the Federal Constitution of 1934, but in spite of the fact that the protection of rights that were considered by nature as "Liquid, Certain and Incontestable" date back to this constitution, at a time prior to the institution of the Mandamus in the national legal system, The protection of this category was done by means of habeas corpus. The intention of this article is to rescue this historicity, from the Empire to the present day. The article was developed from qualitative-quantitative research, as well as bibliographic and documentary research in the areas of civil procedure and environment, and the data collected were analyzed by deductive and inductive methods